Evaluation of Plasmodium vivax Cell-Traversal Protein for Ookinetes and Sporozoites as a Preerythrocytic P. vivax Vaccine - Alves, E; Salman, A; Leoratti, F; Lopez-Camacho, C; Viveros-Sandoval, M; Lall, A; El-Turabi, A; Bachmann, M; Hill, A; Khan, S; Reyes-Sandoval, A (American Society for Microbiology, 2017)
Four different vaccine platforms each targeting the human malaria parasite Plasmodium vivax cell- traversal protein for ookinetes and sporozoites (PvCelTOS) were generated and assessed for protective efficacy. These platforms consisted of a recombinant chimpanzee adenoviral vector ChAd63-PvCelTOS (Ad); a recombinant MVA-PvCelTOS (MVA); a bacteriophage Qβ-PvCelTOS virus-like particle (VLP); and recombinant PvCelTOS protein expressed in eukaryotic HEK293T cells (protein). Inbred BALB/c and outbred CD-1 mice were immunized using the following prime/boost regimens: Ad-MVA, Ad-VLP and Ad-protein. Protective efficacy against sporozoite challenge was assessed after immunization using a novel chimeric rodent Plasmodium berghei parasite. This chimeric parasite (Pb-PvCelTOS) expresses P. vivax CelTOS in place of the endogenous P. berghei CelTOS and produces fully infectious sporozoites. A single A2 immunization in BALB/c and CD-1 mice induced anti-PvCelTOS antibodies which were boosted efficiently using MVA, VLP or protein immunization. High frequencies of PvCelTOS specific IFN-γ and TNF-α producing CD8+ 44 T-cells were induced by all prime/boost regimens in BALB/c but not in CD-1 mice; in CD1 mice they were only marginally increased after boosting with MVA. Despite the induction of anti-PvCelTOS antibodies and PvCelTOS-specific CD8+ 46 T-cell responses, only low protective efficacy against challenge with Pb-PvCelTOS sporozoites was obtained, using any immunization strategy. In BALB/c mice no immunization regimes provided significant protection against a Pb-PvCelTOS chimeric sporozoite challenge. In CD1 mice modest protective efficacy was observed using the Ad-Protein vaccination regimen against challenge with chimeric P. berghei sporozoites expressing either PvCelTOS or P. falciparum CelTOS.